How large is the periablational zone after radiofrequency and microwave ablation? Computer-based comparative study of two currently used clinical devices - Macarena Trujillo; Punit Prakash; Pegah Faridi; Aleksandar Radosevic; Sergio Curto; Fernando Burdio; Enrique Berjano (International Journal of Hyperthermia, 2020)
Purpose To compare the size of the coagulation (CZ) and periablational (PZ) zones created with two commercially available devices in clinical use for radiofrequency (RFA) and microwave ablation (MWA), respectively. Methods Computer models were used to simulate RFA with a 3-cm Cool-tip applicator and MWA with an Amica-Gen applicator. The Arrhenius model was used to compute the damage index (Ω). CZ was considered when Ω > 4.6 (>99% of damaged cells). Regions with 0.6<Ω < 2.1 were considered as the PZ (tissue that has undergone moderate sub-ablative hyperthermia). The ratio of PZ volume to CZ volume (PZ/CZ) was regarded as a measure of performance, since a low value implies achieving a large CZ while keeping the PZ small. Results Ten-min RFA (51 W) created smaller periablational zones than 10-min MWA (11.3 cm3 vs. 17.2−22.9 cm3, for 60−100 W MWA, respectively). Prolonging duration from 5 to 10 min increased the PZ in MWA more than in RFA (2.7 cm3 for RFA vs. 8.3−11.9 cm3 for 60−100 W MWA, respectively). PZ/CZ for RFA were relatively high (65−69%), regardless of ablation time, while those for MWA were highly dependent on the duration (increase of up to 25% between 5 and 10 min) and on the applied power (smaller values as power was raised, 102% for 60 W vs. 81% for 100 W, both for 10 min). The lowest PZ/CZ across all settings was 56%, obtained with 100 W-5 min MWA. Conclusions Although RFA creates smaller periablational zones than MWA, 100 W-5 min MWA provides the lowest PZ/CZ.